Das House Kapital - Grossmann, Volker,Larin, Benjamin,Steger, Thomas M. (University of Fribourg, Switzerland, Faculty of Economics and Social Sciences, 2021)
The housing wealth-to-income ratio has been increasing in most developed economies since the 1950s. We provide a novel theory to explain this long-term pattern. We show analytically that house prices grow in the steady state if i) the housing sector is more land-intensive than the non-housing sector, or ii) technological progress in the construction sector is weaker than in the non-housing sector. Despite growing house prices and housing wealth, the housing wealth-to income ratio is constant in steady state. We hence study the dynamics in the housing wealth-to- income ratio by computing transitions. The model is calibrated separately to the US, UK, France, and Germany. On average, we replicate 89 percent of the observed increase in the housing wealth-to-income ratio. The key for replicating the data is the differentiation between residential land as a non-reproducible factor and residential structure as reproducible factor. The transition process from the calibrated model points to two driving forces of an increasing housing wealth-to-income ratio: i) A long- lasting construction boom that brought about a pronounced build-up in the stock of structures and ii) an increase in the demand for residential land that resulted in surging residential land prices.
http://doc.rero.ch/record/330545
Keywords: Graue Literatur; Housing Wealth; Economic Growth; Wealth-to-Income Ratio; House Price; Land Price